2011
DOI: 10.1111/j.1477-2574.2011.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic vein thrombosis in severe acute pancreatitis: a 2-year, single-institution experience

Abstract: Splanchnic vein thrombosis is a relatively common observation in severe AP and is associated with pancreatic necrosis and peripancreatic collections. Recanalization is observed in almost a third of patients, irrespective of whether or not they receive systemic anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
160
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(174 citation statements)
references
References 10 publications
12
160
1
1
Order By: Relevance
“…The superior mesenteric vein was the least common vessel to be involved, with thrombosis observed in only 4 (15.3%) patients. This pattern of vascular involvement is consistent with previous studies [8,9]. Almost all the previous studies reported the splenic vein to be the most commonly involved vessel.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The superior mesenteric vein was the least common vessel to be involved, with thrombosis observed in only 4 (15.3%) patients. This pattern of vascular involvement is consistent with previous studies [8,9]. Almost all the previous studies reported the splenic vein to be the most commonly involved vessel.…”
Section: Discussionsupporting
confidence: 92%
“…Pleural effusion was also seen in a significantly greater number of patients with SVT, which may be related to a higher degree of local inflammation in AP patients with pleural effusion. Pancreatic and peri-pancreatic necrosis and the associated inflammatory process cause vascular inflammation and infiltration of vessels by inflammatory cells, inducing stasis leading to thrombus formation [8,9]. In our study, consistently with this hypothesis, the presence of necrotizing pancreatitis was significantly associated with a greater probability of developing SVT.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations